I. Kant on religion, faith, god, and church - Belov V. N.; Fakhrudinova E. R. (Кантовский сборник, 2017)
The article analyses the leading concepts and provisions of Kant's philosophy of religion. The findings are based on a comparative analysis of the German philosopher’s major works on the philosophical doctrine of religion, namely Lectures on the philosophical doctrine of religion and Religion within the Boundaries of Mere Reason. The authors trace both the evolution of Kant’s ideas on religion and the consistency and systematicity of changes in the philosopher’s views. The published Lectures confirm the fact that Kant never considered the problems of philosophy of religion as minor ones. When comparing the two major works on religion, one cannot but notice the difference between objects constituting the logic of Kant’s reasoning. In the Lectures, this object is theology as a scientific discipline concerned with knowledge of god, whereas, in Religion, it is believers with their predispositions and capacities, generic and individual characteristics. Not unlike Critiques, where Kant moves from the theoretical to the practical, studies on religion proceed from the theoretical significance of the idea of God considered in the Lectures to the practical aspects of this idea addressed in the Religion. The Lectures contain a vast body of speculative evidence of the existence of God, which is completely absent in Religion. Religion places a much stronger emphasis on the need for the moral perfection of human beings than the Lectures do. However, it would be wrong to assume that the Lectures present a position different from the responsibility of human beings for their own moral condition and its development.